An Analysis of Code-Mixing in Indonesian Movie ‘Imperfect’ - Nurul Agustina; Iskandar Abdul Samad; Tengku Maya Silviyanti (Universitas Syiah Kuala, 2022)
Code-mixing is using two or more languages fluently at the same time by changing from one to another in the span of a single sentence. The purpose of this study is to find out the types and the factors of code-mixing in the movie. The source of the data is code-mixing in English which is inserted into Indonesian utterances committed by the actors in Indonesian movie entitled Imperfect movie: Karier, Cinta Timbangan. The research method used is descriptive-qualitative method with content analysis approach. The instrument that is used to collect the data in this research is observation sheet in the form of observation checklist. The data were analyzed and classified based on the types of code-mixing proposed by Muysken (2000) and the factors of code-mixing proposed by Bhatia and Ritchie (2006). The results of this research showed that the actors in the movie have committed all three types of code-mixing and four factors of code-mixing. There were 95 data for the types of code-mixing and 70 data for the factors of code-mixing. In the types of code-mixing, the most dominant type is insertion with 79 occurrences and the least dominant type is alternation with 3 occurrences. Further, in the factors of code-mixing, the most dominant factor is message-intrinsic factor with 23 occurrences and the least dominant factor is language attitudes, dominance, and security factors with 6 occurrences.